EFISIENSI PENGGUNAAN RADIASI SURYA DAN SEBAGAI DASAR DALAM MODEL JARAK PAGAR(RADIATION USE EFFICIENCY AS BASIS THE CROPS MODELING OF JATROPHA) - Gusti Rusmayadi; . Handoko; Yonny Koesmaryono; Didiek Hadjar Goenadi (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2008)
Plant growth interpretation in term of accumulated intercepted solar radiation and the radiation use efficiency (RUE) was used to study the growth and analysis of Jatropha (Jatropha curcas L.). A number of crop growth simulation models have been developed using the RUE concept to predict crop growth and yield in various environments. These models generally calculate daily biomass production as the product of the quantity of radiation intercepted and RUE. This research was carried out to quantify the RUE, biomass and leaf area index on Jatropha under rainfall condition, four levels of nitrogen fertilizer (N) and three population densities (P) planted twice. The experiments used a systematic Nelder fan design with 9 spokes and 4 – 5 rings were conducted at SEAMEO-BIOTROP field experiment in 2007. Data from the first experiment were used for parameterization and calibration and the second experiment data for model validation. Values of RUE were determined by nitrogen fertilizer and plant density. Based on parameterization, we found that RUE for prediction above ground biomass accumulation of Jatropha were 0.94 (r=0.83) g MJ-1 to 1.3 (r=0.75) g MJ-1. Validation between model prediction and field experimental data showed that model can simulate crop growth and development of Jatropha.